Intra-territorial inequalities in children’s hospital admissions in the Metropolitan area of Santiago, Chile - Manuel Fuenzalida (Unité Mixte de Recherche 8504 Géographie-cités, 2018)
This paper aims to unveil the behavior of inequalities in health among the children population according to socioeconomic groups living in the same territory. The main purpose of the research is to determine if hospital admissions for respiratory diseases present evidence of unequal effects on morbidity of the resident population in the municipalities of the Metropolitan Area of Santiago de Chile (MAS). The entropy index is used in order to present socio-spatial inequalities, proportional differences between mutually exclusive groups, and redistribution potential. Simultaneous observation of the spatial distribution of multiple socioeconomic groups within a territory provides a new lens for approaching the recent studies of inequality in the MAS, and allows to overcome an analysis based only on two antagonistic groups. The main findings show inequality of health damage in residents of different municipalities in the Metropolitan Area of Santiago, Chile. The data shows how the place of residence influences the health inequalities experienced, finding the following configurations: territorial balance; territorial imbalance; territorial inequality; extreme territorial inequality. The differences found in the proportionality of hospital admissions, according to the socioeconomic group do not follow a uniform trend in favor of least vulnerable groups.